Capacity Building dalam Pencatatan Laporan Keuangan Sederhana Bagi Pelaku Usaha Mikro - Rifai, Fuad Yanuar Akhmad; Siswanto, Siswanto; Purwanto, Purwanto; Putri, Sherlly Oktavia Dwi (PELITA NUSA TENGGARA, 2025)
MSMEs that have resilience and are prepared to face economic crises have great potential to absorb labor, contributing to reducing unemployment rates. In this context, efforts to develop MSMEs become an urgent need. The case study in Danurejo Village identified several aspects that require more attention, especially regarding recording financial reports. The main challenges are separating personal and business money more and understanding the benefits of recording simple financial reports. Therefore, community service activities in Danurejo Village aim to increase the capacity of small business actors in recording financial reports. The approach involves education and assistance regarding recording techniques and an in-depth understanding of their benefits for business progress. Daily bookkeeping is integrated into the daily activities of micro-entrepreneurs to provide practical support. The PAR (Participatory Action Research) method implements this activity, ensuring active and collaborative participation between researchers and business actors. The implementation results show increased public understanding and knowledge of the importance of recording simple financial reports. Businesses recognize the real benefits of this practice, strengthening the financial foundation of their businesses and preparing them to face economic challenges. Awareness of the importance of recording financial reports is the key to increasing the competitiveness of small businesses.